Ruptured Anterior Communicating Artery Aneurysm With Untreated Craniopharyngioma: A Case Report. Issue 3 (August 2016) - Zhong, Chuanhong; Ye, Feng; Yin, Senlin; Jiang, Shu
Abstract : Coexistence of intracranial aneurysm and craniopharyngioma has been reported in several patients who have undergone postoperative radiotherapy. However, we present an extremely rare case of ruptured aneurysm of anterior communicating artery (AComA) complicating with naive craniopharyngioma. The blood supply of A2 segment of left anterior cerebral artery was mainly from the right side through AComA in digital subtraction angiography. We suggest that by pressing the A1 segment of left anterior cerebral artery, the tumor imposed heavy burden to the AComA, which promoted the genesis and rupture of this aneurysm.